Деякі питання визнання права як спосіб захисту права власності - Скриннікова, К. О.; Skrynnikova, K. O.; Катерина Скриннікова (Юридичний науковий електронний журнал. - 2024. - № 5. - С. 181-183, 2024)
Досліджено законодавче закріплення визнання права як способу захисту права власності та практичні проблеми реалізації такого способу. Запропоновано розглядати визнання права власності як такий спосіб захисту, метою якого є усунення невизначеності у суб’єктивному праві, та такий що спрямований на надання власнику можливості реалізації своїх прав. А також умовно розподілити підстави пред’явлення позову про визнання права власності на два види. Зазначено, що до першої підстави слід відносити випадки, коли право власності оспорюється або не визнається іншою особою, а до другої підстави слід відносити випадки, коли власник втратив документ який засвідчує його право власності.

The article is devoted to the disclosure of the concept of recognition of the right and analyzes the recognition of the ownership right as a method of protection. The author states that one of the unresolved legal problems of today is the problem of the possibility and proper protection of subjective civil rights. At the legislative level, a number of constructions and mechanisms are provided for, which, in turn, can be used to restore a person's violated property right. The existence of such legal mechanisms for the restoration of violated rights makes it possible to restore the property situation of the participants in civil legal relations. In the article, the author analyzed the legislative consolidation of the protection of property rights, namely the presence of such prerequisites as contestation or non-recognition of existing property rights by another person. During the research, the author proposed to consider the recognition of property rights as a method of protection, the purpose of which is to eliminate uncertainty in subjective law, and which is aimed at providing the owner with the opportunity to exercise his rights. In the article, it is proposed to conditionally divide the grounds for presenting a claim for the recognition of the right of ownership into two types. It is noted that the first reason should include cases when ownership is disputed or not recognized by another person, and the second reason should include cases when the owner lost a document certifying his ownership. The study analyzed the plaintiff who may be sued for the recognition of ownership rights, as well as the defendant in such a lawsuit. In the article, the author asserts about the provided out-of-court possibility of restoring a lost document that confirms a person's right to ownership and suggests ways to implement such a method of protection. According to the results of the research, the author claims that the recognition of the right of ownership is an important way for a person to protect his right, which, in the future, gives the owner the opportunity to fully realize his rights.

Исследовано законодательное закрепление признания права как способа защиты права собственности и практические проблемы реализации такого способа. Предложено рассматривать признание права собственности как способ защиты, целью которого является устранение неопределенности в субъективном праве, и направленный на предоставление владельцу возможности реализации своих прав. А также условно распределить основания предъявления иска о признании права собственности на два вида. Отмечено, что к первому основанию следует относить случаи, когда право собственности оспаривается или не признается другим лицом, а ко второму основанию следует относить случаи, когда владелец потерял документ, удостоверяющий его право собственности.
Some issues of legal recognition as a way of property rights protection
Keywords: визнання права; визнання права власності; захист права власності; способи захисту права власності; позов про визнання права власності; recognition of rights; recognition of ownership rights; protection of ownership rights; methods of protection of ownership rights; claim for recognition of ownership rights; признание права; признание права собственности; защита права собственности; способы защиты права собственности; иск о признание права собственности